Microprocessor controlled display / Mohd. Nizam Abd. Razak - Abd. Razak, Mohd. Nizam (1995)
Today, display systems are widely used in many applications such as in information display services and advertising. There are many types of display systems which are constructed according to the specific needs and applications. One of the common types of display system uses light emitting diodes (LEDs) for displaying specific information and permanent displays. The overall objective of this project is to design and build a prototype display system which is versatile and expandable. The system will be able to communicate with a personal computer for updating the information displayed and commands for controlling the display. The display is to be modular in nature so that it could be easily expanded to increase the amount of information displayed. The display would be able to display information moving from left to right or vice versa, blinking or static. The report will however focus on the basic design of the display section. Specifically, the design of a display controller hardware and firmware for controlling a light emitting diode matrix display is undertaken.